Dose response effect of carbohydrate mouth rinse on 10 km running time trial - Muhammad Saufy Abdul Karim (2018)
Rationale: Previous studies have reported an improvement in performance with carbohydrate (CHO) mouth rinsing compared to placebo. Limited studies have explored dose response effects, with the highest dose used being 14%, and cycling as a common mode of exercise. Purpose: This study investigates the dose response effects of CHO mouth-rinse on 10 kilometre (km) running time trial. Methods: In this double-blinded, randomized, counterbalanced cross-over study, nine recreationally active and healthy men [mean age 23.78 (SD 1.39) years] completed three 10 km running sessions on the treadmill at a self-selected pace. Participants had a five minutes warm up, followed by a 30 seconds (s) mouth-rinse. Thereafter, participants mouth-rinsed for 10 s for every one km of the run completed until the completion of the 10 km. For the first session, participants had a familiarization session using 25 ml of plain water to mouth-rinse. For the second and third sessions, participants were given either 25 ml of 6.4% CHO or 15% CHO solution to mouth-rinse. Heart Rate (HR), Rate of Perceived Exertion (RPE), and time to completion were measured during each session. Results: No significant difference (p = .441) in 10 km running time trial were observed between 6.4% CHO [mean 63.83 (SD 11) min] and 15% CHO [mean 65.91 (SD 13.36) min]. No significant difference were found in HR (p = .440) between 6.4% CHO [mean 162 (SD 7) beats/min] and 15% CHO [mean 158 (SD 13) beats/min]. RPE was not significantly different (p = .084) between 6.4% CHO [median 12 (IQR 1.5)] and 15% CHO [median 14 (IQR 3)]. Conclusion: 15% CHO mouth-rinse did not significantly improve 10 km running time. HR and RPE did not differ significantly between trials.